1997
DOI: 10.1111/j.1348-0421.1997.tb01912.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined Use of Ribotyping, PFGE Typing and IS431 Typing in the Discrimination of Nosocomial Strains of Methicillin‐Resistant Staphylococcus aureus

Abstract: We have previously reported the phenotypic characterization of methicillin-resistant Staphylococcus aureus (MRSA) clinical strains isolated in Malaya University Hospital in the period 1987 to 1989 using antibiogram, coagulase typing, plasmid profiles, and phage typing. Here, we report the analysis of the same strains with three genotyping methods; ribotyping, pulsed-field gel electrophoresis (PFGE) typing, and IS431 typing (a restriction enzyme fragment length polymorphism analysis using an IS431 probe). Ribot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…PFGE with SmaI-cut genomic DNA was carried out as described previously (37), using a CHEF DRII apparatus (Bio-Rad Laboratories) with an electric field strength of ∼6 V/cm and a pulse time of 20 s for 22 h. To differentiate the restriction profile of the genomes of Mu50Ω1 from Mu50Ω2, enzyme AscI or SgrAI was used for DNA digestion. Southern blotting hybridization was carried out as described previously (37). The DNA probe was prepared using primers SAV0813-Fp22 (5′-TTAACTAT-GAGCACGCTATT-3′) and SAV0813-Rp468 (5′- The probes were then labeled with digoxigenin using a DNA labeling kit (Roche).…”
Section: Methodsmentioning
confidence: 99%
“…PFGE with SmaI-cut genomic DNA was carried out as described previously (37), using a CHEF DRII apparatus (Bio-Rad Laboratories) with an electric field strength of ∼6 V/cm and a pulse time of 20 s for 22 h. To differentiate the restriction profile of the genomes of Mu50Ω1 from Mu50Ω2, enzyme AscI or SgrAI was used for DNA digestion. Southern blotting hybridization was carried out as described previously (37). The DNA probe was prepared using primers SAV0813-Fp22 (5′-TTAACTAT-GAGCACGCTATT-3′) and SAV0813-Rp468 (5′- The probes were then labeled with digoxigenin using a DNA labeling kit (Roche).…”
Section: Methodsmentioning
confidence: 99%
“…PFGE was carried out as described previously (35). Electrophoresis was performed for 22 h with a DRII contour-clamped homogenous electric field apparatus (Bio-Rad) with a pulse time of 5 to 40 s. The separated DNA fragments digested with the enzyme SmaI were photographed after being stained with ethidium bromide.…”
Section: Methodsmentioning
confidence: 99%
“…Ichiyama et al reported that MRSAs with several different PFGE patterns were isolated from patients in individual hospitals (15). Yoshida et al suggested that local outbreaks could well be monitored by the combination of PFGE typing and other genomic typing with sufficient resolution power as well as satisfactory references to the biological and evolutionary features of each MRSA isolate (29). Although there was no contact between JMSH, DMSH and SUH personnel and of the distant geographic locations from each other, MRSAs with similar or the same PFGE patterns were isolated from neonates in the NICUs of these hospitals.…”
Section: Discussionmentioning
confidence: 99%